2023
DOI: 10.1002/prot.26495
|View full text |Cite
|
Sign up to set email alerts
|

Metastable alpha‐rich and beta‐rich conformations of small Aβ42 peptide oligomers

Abstract: Probing the structures of amyloid‐β (Aβ) peptides in the early steps of aggregation is extremely difficult experimentally and computationally. Yet, this knowledge is extremely important as small oligomers are the most toxic species. Experiments and simulations on Aβ42 monomer point to random coil conformations with either transient helical or β‐strand content. Our current conformational description of small Aβ42 oligomers is funneled toward amorphous aggregates with some β‐sheet content and rare high energy st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 88 publications
(108 reference statements)
0
1
0
Order By: Relevance
“…Recently, Berardet et al found that the initial state of conformation, oligomerization, and quality of the hIAPP can greatly impact the aggregation kinetics . Different oligomeric conformations have been predicted using several analytical techniques like TEM, thioflavin T (ThT) fluorescence spectroscopy, or the machine-learning AlphaFold2 method. , …”
Section: Results and Discussionmentioning
confidence: 99%
“…Recently, Berardet et al found that the initial state of conformation, oligomerization, and quality of the hIAPP can greatly impact the aggregation kinetics . Different oligomeric conformations have been predicted using several analytical techniques like TEM, thioflavin T (ThT) fluorescence spectroscopy, or the machine-learning AlphaFold2 method. , …”
Section: Results and Discussionmentioning
confidence: 99%